STUDI PENGEMBANGAN MODEL PERENCANAAN RUSUNAWA DI PROVINSI JAWA TENGAH - Sofyan St. B., Afriyanto (VITASPHERE, 2012)
The planning of housing and settlement based on optimizing urban land use has already been decided in Town Planning Regulation. Rental multi level housing for low income is under Government Program of Urban Renewal. This houseng model is relatively new in Indonesia in particular for low economic income. The problem is this economic layer society culturally lives on the ground and moves to live off the ground with minimum space. As a result the movement of economic, social and cultural activity is getting narrower and potention ally give cultural shock